DIAGNOSTIC ACCURACY IN ACUTE APPENDICITIS: COMPARISON BETWEEN CLINICAL IMPRESSION AND ULTRASOUND FINDINGS - Mufti, Tariq S; Akhtar, Saleem; Khan, Khalid; Raziq, Fazle; Rehman, Zia- -ur; Ahmed, Ijaz (Journal of Ayub Medical College Abbottabad, 1996)
A cross-sectional study to determine the diagnostic accuracy of clinical impression and graded compression abdominal ultrasonography in acute appendicitis used individually or complementary to each other was conducted in a busy surgical unit. Eighty-nine cases subjected to categorized clinical impression and ultrasonography preoperatively achieved fairly high sensitivity (84.3% and 81.81% respectively) but low specificity (23.68% and 38.23%) with an overall negative predictive value of 31%, implying it to be a poor indicator to avoid negative appendectomies.